Herpes zoster ophthalmicus following onabotulinumtoxinA administration for chronic migraine: A case report and literature review. (April 2015) - Gadient, Paul M; Smith, Jonathan H; Ryan, Stephen J
Background: There is a growing body of literature documenting local herpes zoster outbreak following procedures. The mechanism underlying these outbreaks remains elusive. We present a case of zoster following onabotulinumtoxinA (BTX) for migraine and a literature review. Methods: Chart and literature review. Case: A 72-year-old woman with chronic migraine received BTX injections for 3 years without incident. She had a history of thoracic zoster with subsequent post-herpetic neuralgia. In August 2013, 48 hours after receiving BTX injections, she developed a painful rash in the right V1 distribution consistent with herpes zoster ophthalmicus. One week later the rash had resolved without treatment. Literature review: We identified 65 (including 2 from Juel-Jenson) cases of zoster reactivation following minor procedures. These cases tend to be in young patients without specific risk factors. Outbreaks characteristically occur at the level of exposure to local trauma. Discussion: Our review suggests that local trauma, regardless of the nature of stimuli, may be sufficient for zoster reactivation. We hypothesize that the stressors in these reported cases exert a local epigenetic influence on viral transcription, allowing for viral reactivation. Conclusion: Zoster is a potential complication of BTX administration for chronic migraine in adults. Physician awareness can reduce the significant morbidity associated with this disease.